Chinese families : tradition, modernization, and change - Kan, Man Yee; Blair, Sampson Lee (Contemporary perspectives on family research, 2021)
Over the past half of a century, Chinese societies have undergone a tremendous amount of social, political, and economic change, which have also been a catalyst for substantial shifts in fundamental structures and processes within Chinese families. This edited collection focuses on the continuities and changes in gender and intergenerational relations of Chinese families in Greater China. Paying close attention to families in Greater China, including the People's Republic of China, Hong Kong, and Taiwan, the authors address a wide array of topics, including marriage patterns, cohabitation, rural-urban variations in family structures, fertility aspirations, spousal relationships and marital quality, and more. Collectively, the chapters point to the dynamic, diverse, and evolving nature of Chinese families, and also provide considerable insight into their future trajectories.